2017
DOI: 10.18488/journal.aefr.2017.711.1075.1092
|View full text |Cite
|
Sign up to set email alerts
|

Trade Liberalization and Gender Inequality in Emerging Economies - from the Perspective of Sustainable Development Goals

Abstract: Article History JEL Classification O50, F16, F60. The study identifies the effect of trade liberalization on gender inequality in labor market, welfare, and empowerment in the emerging economies considering the significance of gender inequality issue in sustainable development goals (SDGs). It uses global gender gap index (GGGI) and its four sub-indexes namely economic participation and opportunity, education, health and politics as indicators of gender inequality in different aspects. Due to the problem of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
4
0
1
Order By: Relevance
“…Por el lado contrario, también se han encontrado casos en los que la brecha de género salarial aumenta como consecuencia del libre comercio. Como Sepehrivand (2017) y Fatema et al (2018) observaron un conjunto de países en desarrollo, obtuvieron resultados contrarios a este primer autor; es decir, registraron un aumento en la desigualdad salarial. En este caso, el periodo observado fue más amplio, de 1994 a 2014 -frente al periodo de 2001 a 2013, estudiado por Sepehrivand-, y el número de países fue menor -dieciséis frente a treinta y cinco-.…”
Section: B) Incrementos En La Brecha Salarial De Género Como Consecue...unclassified
“…Por el lado contrario, también se han encontrado casos en los que la brecha de género salarial aumenta como consecuencia del libre comercio. Como Sepehrivand (2017) y Fatema et al (2018) observaron un conjunto de países en desarrollo, obtuvieron resultados contrarios a este primer autor; es decir, registraron un aumento en la desigualdad salarial. En este caso, el periodo observado fue más amplio, de 1994 a 2014 -frente al periodo de 2001 a 2013, estudiado por Sepehrivand-, y el número de países fue menor -dieciséis frente a treinta y cinco-.…”
Section: B) Incrementos En La Brecha Salarial De Género Como Consecue...unclassified
“…From a long-term perspective, the influence of openness strategies on gender findings may be of concern, as there is growing evidence that empowering women increases education and improves children's outcomes (Duflo, 2003;Juhn, Ujhelyi, & Villegas-Sanchez, 2014;Qian, 2008;Thomas, 1990). Two mainstream theories of international trade can be used to explain the impact of trade openness on gender imbalance (Fatema et al, 2017). According to the Heckscher-Ohlin theory, countries should focus on producing commodities for which they have plentiful factors of production.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…As a result, trade liberalization improves women's health and education levels. Trade increases the government's revenue, allowing it to spend more on health, education and other social services (Fatema et al, 2017). As a result of the rapid growth effect of trade on education, many bilateral, regional and multilateral trade agreements have integrated provisions on trade and investment in education services which together make up the legal and institutional framework defining and controlling the openness of trade in educational services.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Takian and Akbari‐Sari (2016), Tamsma and Costongs (2018), Dietler et al (2019), Lee and Kim (2019), Sipido and Nagyova (2020) have also discussed the importance of public health in achieving SDGs. Fatema, Li, and Islam (2017) identified the effect of trade openness on gender inequality, empowerment and welfare in the emerging economies considering the SDGs. It was observed that trade openness had increased gender inequality in labor market in emerging economies but reduced inequality in high growth countries.…”
Section: Review Of Previous Literaturementioning
confidence: 99%